Role of rural tourism and agriculture for development of rural, protected areas - Baranyai, Olga; Baranyai , Gábor (Journal for Geography, 2013)
The main challenge in rural areas currently is facing migration and unemployment. Inhabitants of the traditional Őrség region also face this serious problem. The aim of this paper is to reveal problems in the region highlighting the two pillars of local rural development solutions; the current situation and opportunities for tourism and agriculture development. The opinion of local inhabitants acquired through questionnaires bare a special role in this search for solutions. Given its geographic location, success of the region’s rural development may also be achieved through cross-border initiatives and cooperation.
Keywords: rural development; borderlands; sustainable development; sustainable agriculture; rural tourism; ecotourism; Őrség